THE EFFECT OF THE TAXATION SYSTEM AND LOVE OF MONEY ON STUDENTS' PERCEPTIONS OF TAX EVASION - Nuri Annisa Fitri; Hisbullah Basri; Kusminaini Armin; Putri Anzella (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to determine and analyze how the Taxation System and Love of Money affect Student Perceptions regarding Tax Evasion. This study has two independent variables, namely the taxation system and love of money and one dependent variable, namely student perceptions regarding tax evasion. Students of the Faculty of Economics and Business, Tridinanti University are the population in this study. Students in the S1 Accounting Study Program, S1 Management and D3 Finance and Banking. The sampling technique for this study was purposive sampling. The sample used in this study was 128 people. The type of data in this study is primary data in the form of a questionnaire. The method of collecting this questionnaire data is in the form of a google form which is distributed online to students. The data obtained will be processed through the IBM SPSS App version 20. Based on the results of the hypothesis test, it can be said that the first hypothesis, the tax system variable (X1) has a significant effect on the tax evasion variable (Y). Where, the results of the t-test value sig. of 0.000 < 0.05. The second hypothesis, the love of money variable (X2) has a significant effect on the tax evasion variable (Y). Where, the results of the t-test sig. value of 0.000 < 0.05. The third hypothesis, the F value of 0.000 < 0.05. This means that the tax system and love of money have an effect on tax evasion.